Repositioning Vocational and Technical Education in Nigeria: Work-Based Versus Work-Place Learning and Skill Acquisition Order - Budi Santosa; Tajudeen Adebisi (Journal of Vocational Education Studies, 2022)
Vocational and technical education (VTE) is a stratum of education system that deals directly with acquisition of skills for work. Nigeria’s National Policy on Education (NPE) in Section 7 Numbers 40 to 57 expansively stresses the need for VTE with a view to producing formidable workforce with relevant vocational and technical competences necessary for sustainable national development. On this premise, this paper underscores repositioning VTE in Nigeria. This article conceptually explores the similarities as well as the differences between work-based learning and work-place learning. How these two concepts result into vocational and technical skill acquisition with their attendant demands forms a major section of this paper.  The paper views that if the opportunities for job skills acquisition offered by work-based and work-place learning could be purposively harnessed into the nation’s educational programme, the ever-rising unemployment rate in the country would drastically be alleviated.